The Arithmetic Basis of Special Relativity - II - Greenspan, Donald (University of Wisconsin-Madison Department of Computer Sciences, 1975)
In a previous paper, it was shown that under the assumption that both particle and rocket frame motions were in the X-direction only, then all the basic concepts and results of special relativity were obtainable from arithmetic processes only. In this paper, the arithmetic approach is extended to more general particle and rocket frame motions. Particular attention is directed toward velocity, acceleration, proper time, momentum, energy and 4-vectors in both spacetime and Minkowski space, and to relativistic generalizations of Newton's second law.